Analysis of the contribution of the Colsubsidio family compensation fund, to education in Bogotá 2016-2018 (2020)
Access to education in Colombia is limited by various factors, including the characteristics of the department in which it is located and the level of education to which it refers, in addition to the important factor such as the resources of families, The educational level of a Colombian depends a lot on this. According to the Ministry of Education (2020), the education system in Colombia is organized into four levels: initial education and comprehensive early childhood care, pre-school education, basic education, secondary education lasting two years, and higher education. Poverty in a family is considered to be directly related to the level of education among individuals in each family, but it is in the families with the most scarce resources that it is evident that the state is not completely efficient in its work of guaranteeing access to high-quality and efficient education for all Colombians This is why the system generates agreements with non-state entities but service providers that allow it to guarantee an increase in the coverage of demand and its quality, in order to meet the objectives. As is the case with Colsubsidio and its agreements with the state in the provision of social service in terms of education, a non-profit entity focused on contributing to the country to achieve the 2030 agenda, in addition to the mitigation of social gaps, with all the subsidies and benefits it offers to all Colombians. The organization for the analysis period had 4 schools of its own, 27 social kindergartens focused on early childhood care, and several institutions in its administration oriented with a humanist approach to contribute to the improvement of the quality of life of Bogota and Colombians, and to the alleviation of social gaps and hence poverty in the Colombian territory. With support at all levels of study, initial, basic, middle and higher education, providing opportunities for more than 25,000 students of all ages and levels of study by the end of 2018.